2010
DOI: 10.2174/157340310791658802
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis, Neurogenesis and Neuroplasticity in Ischemic Stroke

Abstract: Only very little is know about the neurovascular niche after cardioembolic stroke. Three processes implicated in neurorepair: angiogenesis, neurogenesis and synaptic plasticity, would be naturally produced in adult brains, but also could be stimulated through endogen neurorepair phenomena. Angiogenesis stimulation generates new vessels with the aim to increase collateral circulation. Neurogenesis is controlled by intrinsic genetic mechanisms and growth factors but also ambiental factors are important. The lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(79 citation statements)
references
References 71 publications
1
74
0
4
Order By: Relevance
“…Hypoxia and angiogenesis close relationship also plays an important role in the brains of patients who survived from stroke, being microvessel density correlated positively with survival. Increased synthesis of proangiogenic factors like FGF-2, PDGF and VEGF (and their receptors) is also seen in this context, corroborating the importance of angiogenesis in several ischemic conditions [94].…”
Section: Accepted Manuscriptsupporting
confidence: 74%
“…Hypoxia and angiogenesis close relationship also plays an important role in the brains of patients who survived from stroke, being microvessel density correlated positively with survival. Increased synthesis of proangiogenic factors like FGF-2, PDGF and VEGF (and their receptors) is also seen in this context, corroborating the importance of angiogenesis in several ischemic conditions [94].…”
Section: Accepted Manuscriptsupporting
confidence: 74%
“…VEGF-A, which induces angiogenesis, also appears to support neurogenesis (Fabel, et al, 2003,Font, et al, 2010,Jin, et al, 2002). We previously found that in young mice, both supra-lactate threshold exercise and lactate itself induced brain VEGF-A gene expression (E, et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, following permanent occlusion of the MCA, endothelial cells surrounding the infarcted area have been observed to initiate proliferation as early as 12-24 h post infarct. 24 Correspondingly, an increase in vessel density was observed in the peri-infarcted region 3 days after the ischaemic insult.…”
Section: Discussionmentioning
confidence: 99%